(untitled) (Global Journal of Human-Social Science, 2014)
The purpose of the study is to examine the vulnerability to poverty of female headed households by way of making comparisons with their male counterparts in rural Ethiopia. It further looks through the determinants of vulnerability to poverty in female headed households. It is based on the Ethiopian Rural Household Survey from 1999-200. On average 38 percent of households out of the total sampled households are highly vulnerable to poverty and 16.38 percent of the non poor are highly vulnerable to poverty. But based on the recent data used for this study only 35.26 percent of households in rural Ethiopia are poor. This shows that expected poverty is much higher than the point in time estimates of poverty, which connotes the importance of forward looking poverty analysis. The mean vulnerability for all households is also high. This means the households have a higher probability to be poor or remain poor. The mean vulnerability for Female Headed Households is higher than that of Male Headed Households. This shows that Female Headed Households are more vulnerable to poverty than Male Headed Households. Hence, gender-sensitive poverty alleviation policies that enhance endowments such as those that increase livestock ownership, land productivity, education level, and ability to control fertility should be the key ingredients of a poverty reduction strategy in rural Ethiopia.